2021
DOI: 10.3390/medicina57111223
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Telomeric Zinc Finger-Associated Protein Expression in Adenocarcinoma and Squamous Cell Carcinoma of Lung

Abstract: Background and Objectives: Telomeric zinc finger-associated protein (TZAP) is a telomere regulation protein, previously known as ZBTB48. It binds preferentially to elongated telomeres, competing with telomeric repeat factors 1 and 2. TZAP expression may be associated with carcinogenesis, however; this study has not yet been performed in lung cancer. In this study, we examined the clinicopathological and prognostic values of TZAP expression in non-small cell lung cancer (NSCLC). Materials and Methods: Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, there was a limited amount of detail about TZAP expression in each cancer. In lung adenocarcinoma, lower TZAP expression was associated with a higher T stage, inducing a poorer prognosis [23]. Additionally, a shorter overall survival was found in cervical cancer with a lower TZAP expression, especially at the N1 stage [22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, there was a limited amount of detail about TZAP expression in each cancer. In lung adenocarcinoma, lower TZAP expression was associated with a higher T stage, inducing a poorer prognosis [23]. Additionally, a shorter overall survival was found in cervical cancer with a lower TZAP expression, especially at the N1 stage [22].…”
Section: Discussionmentioning
confidence: 97%
“…Compared to normal tissue, TZAP mRNA expression was increased in HCC tissue; however, it was not significant. We previously studied TZAP expression in other cancers, such as colorectal cancer [19], cervical cancer [22], and lung cancers [23], using TCGA data or patient tissues. In these cancers, TZAP expression levels were slightly increased compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…13 Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for 85% of all cases. 14 Many causative factors for lung cancer have been identified, including active smoking, secondhand smoke, occupational agents, radiation, and environmental pollutants. 15 They may influence telomere regulation in human disease especially in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that deregulation of telomere length has the potential to serve as a prognostic marker in patients with NSCLC. 14,16 Therefore, we analyzed, for the first time, the clinical value of telomere regulatory genes in NSCLC.…”
Section: Introductionmentioning
confidence: 99%